Extraction of Hydroxyapatite from Fish Scales and Its Integration with Rice Husk for Ammonia Removal in Aquaculture Wastewater - Sofiah Hamzah; Norhafiza Ilyana Yatim; Maslinda Alias; Asmadi Ali; Nazaitulshila Rasit; Azzam Abuhabib (Universitas Gadjah Mada, 2019)
Aquaculture plays an important role in providing food and generate high income in many developing countries but the abundance of ammonia discharged from aquaculture wastewater gives the problem to the environment. This study focused on the extraction of hydroxyapatite (HAp) from fish scales and its modification with rice husk to produce bio-adsorbent for ammonia removal from aquaculture wastewater. The comparison has been made for the HAp preparation via microwave irradiation, alkaline heat treatment, and thermal decomposition method. X-ray Diffraction (XRD) and Fourier Transform Infrared Spectroscopy (FTIR) were used to analyze the surface chemistry and crystallinity of HAp, respectively. While the morphology of the HAp was observed under a Scanning Electron Microscope (SEM). Hydroxyapatite extracted via thermal decomposition method shows the best performance about 79% of ammonia removal at 210 min contact time which selected for coating agent of rice husk (RH/HAp) and was successfully removed 84% at 60 min saturation time. The result shows thermal decomposition is the best technique to extract HAp from fish scales and its integration with rice husk exhibited a better performance of bio-adsorbent. The findings of this study provide useful fundamental knowledge and platform for the development and improvement of aquaculture wastewater treatment system in the future.